Promoting content variety in MOOCs: increasing learning outcomes with podcasts - Köhler, Daniel; Serth, Sebastian; Meinel, Christoph (Frontiers in Education, 2024)
Online education has become an integral part of everyday life. As one form of online education, traditional Massive Open Online Courses mostly rely on video-based learning materials. To enhance accessibility and provide more variety of the learning content, we studied how podcasts can be integrated into online courses. Throughout three studies, we investigated the acceptance and impact of podcasts made available to learners on the online education platform openHPI. Throughout the studies we applied different methodologies, such as a Posttest-Only Control Group study, and a Static-Group Comparison. In the initial two studies, we identified that podcasts can serve as reasonable addition to MOOCs, enabling additional learning just as well as videos, and investigated the optimal podcast design for our learners. In one of our six-week courses on cybersecurity with more than 1,500 learners, alongside the third study, we identified that consuming an additional podcast can increase learning outcomes by up to 7.9%. In this manuscript, we discuss the applied methodologies and provide reasoning behind design decisions concerning, e.g., the podcast structure or presentation to be taken as inspiration for other educators.